Strongly coupled plasmonic modes on macroscopic areas via template-assisted colloidal self-assembly - Hanske, Christoph; Tebbe, Moritz; Kuttner, Christian; Bieber, Vera; Tsukruk, Vladimir V.; Chanana, Munish; Koenig, Tobias A. F.; Fery, Andreas (Nano Letters, 2014)
We present ensembles of surface-ordered nanoparticle arrangements, which are formed by template-assisted self-assembly of monodisperse, protein-coated gold nanoparticles in wrinkle templates. Centimeter-squared areas of highly regular, linear assemblies with tunable line width are fabricated and their extinction cross sections can be characterized by conventional UV/vis/NIR spectroscopy. Modeling based on electrodynamic simulations shows a clear signature of strong plasmonic coupling with an interparticle spacing of 1-2 nm. We find evidence for well-defined plasmonic modes of quasi-infinite chains, such as resonance splitting and multiple radiant modes. Beyond elementary simulations on the individual chain level, we introduce an advanced model, which considers the chain length distribution as well as disorder. The step toward macroscopic sample areas not only opens perspectives for a range of applications in sensing, plasmonic light harvesting, surface enhanced spectroscopy, and information technology but also eases the investigation of hybridization and metamaterial effects fundamentally.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electromagnetic simulations; gold nanoparticle chains; protein coating; strong plasmon coupling; superradiant and subradiant modes